Policing racist crime and violence : a comparative analysis - Oakley, Robin; European Monitoring Centre on Racism and Xenophobia (EUMC, 2005)
Summary (s. 4-7).
Keywords: rasismi : EU-maat; muukalaisviha : EU-maat; rotusyrjintä : EU-maat; väkivalta : EU-maat; syrjintä : EU-maat; asuminen : EU-maat; työllisyys : EU-maat; koulutus : EU-maat; yhdenvertaisuus : EU-maat